Coordination‐Self‐Assembly Approach toward Aggregation‐Free Metal Nanoparticles in Ordered Mesoporous Carbons. Issue 3 (7th December 2018) - Wu, Wei; Yi, Yikun; Wang, Tao; Gao, Tunan; Huo, Qisheng; Song, Shuyan; Li, Mingtao; Qiao, Zhen‐An
Abstract: Multifunctional ordered mesoporous carbon materials that feature high surface area, uniform pores, good conductivity of the carbon skeletons, and specific host‐gust interactions, which are of interest for a wide variety of applications, for instance, catalysis, photonics, bioscience, and energy storage, are presented. Here, we establish a facile and generalizable "coordination‐assisted self‐assembly" for encapsulation of aggregation‐free and highly dispersed metal nanoparticles inside the mesoporous carbon frameworks. The choice of pyrogallol as phenolic resin precursor is essential for the in situ encapsulation, because the strong coordination between the three hydroxide groups of pyrogallol and metal ions favors the immobilization of transition metal into the mesopores, and then suppress the sintering of metal nanoparticles at high carbonization temperatures. The metal supported mesoporous composites possess the very high loading content of 1.25 %–7.27 %, tiny particle sizes of 4.3–15.6 nm and high surface area of 475–589 m 2 /g. The unique structure in deed endows high sulfur loading content in the conductive mesoporous carbon channels, and meanwhile metal nanoparticles as catalyst effectively promotes the electrochemical conversion of polysulfides, resulting in a high reversible capacity, excellent rate capability and good cycling stability for Li−S batteries. Abstract : A coordination‐assisted self‐assembly strategy allows the synthesis of Co‐mesoporous carbon nanocomposites with well‐dispersed Co nanoparticles at high loading content. The sintering of Co nanoparticles is restricted by both mesopores and coordination bonds. The porous skeleton of the composite, leading to a high surface area and high loading of catalyst nanoparticles, makes it suitable as a host material for active sulfur in Li−S batteries.